Restraining permanent sovereignty over natural resources - Petra Gümplová (Enrahonar: Quaderns de Filosofia, 2014)
The paper examines the international law principle of the permanent sovereignty over natural resources from a critical perspective of its conflict with demands for global environmental protection and sustainability. It is argued that state framed resource sovereignty per se does not represent an obstacle in the path of greater global environmental justice. The principle is strongly justified as a distinct economic expression of post-war state sovereignty and the ramification of the universalization of such principles as decolonization, self-determination, territorial rights, and sovereign equality of states. It is instead the interpretation of sovereignty and the set of practices established in the name of permanent sovereignty over natural resources that undermine international environmental law – the extension of sovereign resource rights beyond state borders, the continuous priority of unrestricted resource rights and development rights over international standards for environmental protection and sustainable use of resources, and the failure to reinforce notions and principles, both conceptually and legally, that better correspond to the global nature and comprehensive demands of ecological systems. The paper argues that the plausibility of resource sovereignty depends on the interpretation of the concept of sovereignty and how it incorporates self-limiting standards in its exercise. A parallel is established between limiting resource sovereignty using environmental sustainability standards and ecological stewardship and human rights as a widely accepted constraint on the exercise of state power over the population.